Verifying exchange rate regimes - Frankel, Jeffrey A., 1952- 05.11.1952-; World Bank Development Research Group Macroeconomics and Growth (Policy research working paper, 2000)
One reason intermediate exchange rate regimes have fallen out of favor is that they are not transparent or easy to verify. A simple peg or a simple float may be easier for market participants to verify than a more complicated intermediate regime